Niveles de escritura; niveles de lectura. La funcionalidad de la escritura publicitaria en la sala capitular de la catedral de Burgos. Entre la gótica minúscula y la prehumanística - García Morilla, Alejandro (Scrineum, 2026)
The epigraphic complex of the chapter hall of the Cathedral of Burgos has an interesting epigraphic program that, more often than not, has gone unnoticed. First, because for a long time its inscriptions were covered by the tapestries that covered its walls. Second, because one of the inscriptions has writing in small, small letters that makes it difficult to locate and read. This article addresses its comprehensive study, placing special emphasis on the paleographic analysis and the functionality of these inscriptions. The particular phenomenon of graphic emergence experienced during the 15th and 16th centuries, the transcendent changes that they will bring about in advertising writing and the architectural and functional changes that occur in the cathedral serve to understand the role that writing had as a mechanism of moral suasion. All of this motivated by the transformative climate of the pontificates of bishops Pablo de Santamaría and Alonso de Cartagena.